The design and development of a multimedia reading application for pre-schoolers as a foundation in the area of TVET - Suhaizal, Hashim; Nur Zahira, Mohamed Zahir; Nuraini Hanisah, Maleki; Mohd Hasril, Amiruddin; Mohd Erfy, Ismail; Eh Phon, Danakorn Nincarean (Semarak Ilmu Publishing, 2025)
The greatest time for this is during early childhood schooling, when children are just beginning to become aware of their job options and form an imagination about the careers, they are interested in. In order to prepare pre-schoolers for their future employment, Technical and Vocational Education and Training (TVET) aims to expand their knowledge and skill sets. Technology development also aids in these preschool students' knowledge and skill development in preparation for their future employment, particularly in TVET. At this preschool stage, their reading skills is essential for learning the TVET sector since it aids in their understanding of the subject that piques their interest. Yet, there are a number of reasons why they can struggle to read, including a lack of prior book experience, speech or hearing problems, and a lack of phonemic awareness. This design and development research (DDR) methodology was chosen to assist pre-schoolers in learning to read as a foundational skill in the field of TVET. The researcher focused on the development of multimedia applications for the teaching and learning process using a quantitative approach through ADDIE Model instructional design. The researcher used a random sampling technique to select three academic staff members with the required TVET educational credentials. This sample includes two academics with experience and skill in multimedia creation, as well as a preschool teacher from an appropriate educational institution, so the feedback gained is adequate to obtain precise comments and points of view. Data were acquired and assessed using frequency and percentage values based on a checklist form that was given. To facilitate data analysis, each item is categorised, and frequency information is quantified as a percentage. Professionals who believe that this multimedia application is useful as one of the self-learning mediums have responded favourably to the study's findings about how this multimedia application functions in terms of assisting pre-schoolers in learning to read from the aspects of content design, interaction, and interface. The study's conclusions can be used as a guide by anyone, especially when it comes to encouraging pre-schoolers’ TVET growth.